1970
DOI: 10.2307/1366475
|View full text |Cite
|
Sign up to set email alerts
|

Energy Requirements for Existence in Relation to Size of Bird

Abstract: Standard metabolism is the energy requirement, usually measured over short periods, of an individual at complete rest and in a postabsorptive state and is of considerable importance to physiologists. Of greater ecological interest, however, is the energy requirement of normal activities under free-living conditions. This may be approximated (within about 13 per cent in the Blue-winged Teal, Arm-~ discors; Owen 1968) by measuring the rate of food utilization over long periods of time of individuals confined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
4

Year Published

1973
1973
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(90 citation statements)
references
References 19 publications
3
82
1
4
Order By: Relevance
“…It is unlikely that these high levels were due to the testing procedure or to any systematic error in the apparatus. The BMR of Long-eared Owls Asio otus measured with the same equipment, were consistently lower than the Aschoff & Pohl (1970( ) prediction (Wijnandts 1984.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…It is unlikely that these high levels were due to the testing procedure or to any systematic error in the apparatus. The BMR of Long-eared Owls Asio otus measured with the same equipment, were consistently lower than the Aschoff & Pohl (1970( ) prediction (Wijnandts 1984.…”
Section: Resultsmentioning
confidence: 64%
“…Assimilation efficiencies for one Oystercatcher were 87% and 89%, and for the other bird 82%, at air temperatures between 10 and 15°C. To estimate the EM (Kendeigh 1970) of our experimental shorebirds, we assumed that their average assimilation efficiency was 85 %. Table 5 shows the dependence of EM on air temperature.…”
Section: Food Consumption In Outdoor Cagesmentioning
confidence: 99%
See 1 more Smart Citation
“…McNab (1963) found that the size of the home range of herbivorous mammals of a given trophic category also varies as the threefourths power of body weight, so we may infer that total energy consumption does too. For birds, Helms (1968) found a similar relationship for total metabolism, bu t Kendeigh (1970), using realistic temperature stress, found the total metabolism of large birds relatively overestimated by the usual equations. Their lesser amount of active flying should at least partly compensate, though, as should the smaller proportion of energy used for growth (implied by their grea ter longevi ty ) .…”
Section: Energy Relationshipsmentioning
confidence: 80%
“…In that model a major limitation to the precision of population energy estimates was the wide confidence intervals associated with the bioenergetics equations of Kendeigh (1970). In this study these equations have been replaced by more recent ones based on considerably more extensive data (Kendeigh et al, 1977).…”
Section: Methodsmentioning
confidence: 99%